2010
DOI: 10.1007/s00359-010-0526-4
|View full text |Cite
|
Sign up to set email alerts
|

Detecting substrate engagement: responses of tarsal campaniform sensilla in cockroaches

Abstract: Sensory signals of contact and engagement with the substrate are important in the control and adaptation of posture and locomotion. We characterized responses of campaniform sensilla, receptors that encode forces as cuticular strains, in the tarsi (feet) of cockroaches using neurophysiological techniques and digital imaging. A campaniform sensillum on the fourth tarsal segment was readily identified by its large action potential in nerve recordings. The receptor discharged to contractions of the retractor ungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
2
27
0
2
Order By: Relevance
“…In a metachronal gait, a hindmost leg steps first, and each successive ipsilateral leg lifts off the ground immediately after its posterior neighbor touches down, suggesting that the legs are coordinated mainly by feedback (Borgmann et al, 2007;Borgmann et al, 2009). A mechanism for this was recently demonstrated in the cockroach P. americana by Zill and co-workers (Zill et al, 2010). They found that as a posterior foot sets down at the end of its swing phase, it touches down near the place where its anterior neighbor is reaching its posterior extreme position at the end of its stance phase.…”
Section: Gait Controlmentioning
confidence: 90%
See 1 more Smart Citation
“…In a metachronal gait, a hindmost leg steps first, and each successive ipsilateral leg lifts off the ground immediately after its posterior neighbor touches down, suggesting that the legs are coordinated mainly by feedback (Borgmann et al, 2007;Borgmann et al, 2009). A mechanism for this was recently demonstrated in the cockroach P. americana by Zill and co-workers (Zill et al, 2010). They found that as a posterior foot sets down at the end of its swing phase, it touches down near the place where its anterior neighbor is reaching its posterior extreme position at the end of its stance phase.…”
Section: Gait Controlmentioning
confidence: 90%
“…Noah and his colleagues cut the afferent nerves in a cockroach's hind legs at the level of the femur, removing feedback from the campaniform sensilla in the tibia that are responsible for coordinating the metachronal gait (Zill et al, 2010). Animals with this manipulation walked with abnormal gaits, as the hind legs stepped very irregularly relative to motions of the other legs.…”
Section: Gait Controlmentioning
confidence: 99%
“…For detailed study of Groups 3 and 4, the cuticle of the dorsal trochanter was further dissected and isolated. Specimens were then treated with 1 M potassium hydroxide for a minimum of 1 h. Preparations were fixed in 4% formalin and placed in Conray (a radiopaque dye that can be used as a clearing agent for insect cuticle; Zill et al 2010) and then viewed and imaged by standard light photomicrographic techniques. Specimens were also imaged by confocal microscopy with a Leica TCS SP5 II microscope at the Marshall University microscopy facility.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…In insects, both temporal and spatial co-ordination among legs is known to depend on sensory feedback (Wendler, 1964;Cruse, 1990;Ritzmann and Büschges, 2007), involving information about limb posture (Wong and Pearson, 1976;Cruse et al, 1984), load (Borgmann et al, 2009;Zill et al, 2009;Zill et al, 2012) and ground contact (Zill et al, 2010;Theunissen and Dürr, 2013). Thus the second objective of this study was to reveal the contribution of a proprioceptive hair field on the accuracy of spatial co-ordination between middle and hindlegs.…”
Section: Introductionmentioning
confidence: 98%